Beta particle energy spectra shift due to self-attenuation effects in environmental sources - Thomas Theakston Alton; Stephen David Monk; David Cheneler (Nuclear Engineering and Technology, 2017)
In order to predict and control the environmental and health impacts of ionizing radiation in environmental sources such as groundwater, it is necessary to identify the radionuclides present. Beta-emitting radionuclides are frequently identified by measuring their characteristic energy spectra. The present work shows that self-attenuation effects from volume sources result in a geometry-dependent shift in the characteristic spectra, which needs to be taken into account in order to correctly identify the radionuclides present. These effects are shown to be compounded due to the subsequent shift in the photon spectra produced by the detector, in this case an inorganic solid scintillator (CaF2:Eu) monitored using a silicon photomultiplier. Using tritiated water as an environmentally relevant, and notoriously difficult to monitor case study, analytical predictions for the shift in the energy spectra as a function of depth of source have been derived. These predictions have been validated using Geant4 simulations and experimental results measured using bespoke instrumentation.